Antecedents of inflammation biomarkers in preterm newborns on days 21 and 28. (23rd December 2015) - Leviton, Alan; Allred, Elizabeth N.; Fichorova, Raina N.; Kuban, Karl C.K.; O'Shea, T. Michael; Dammann, Olaf
Abstract: Aim: Most studies of systemic inflammation in very preterm newborns focus on assessments made during the first two weeks. The purpose of this study was to identify some of the antecedents of systemic inflammation evident during postnatal weeks three and four. Methods: We measured the protein concentrations in blood spots collected on postnatal days 21 ( N = 176) and 28 ( N = 157) from infants born before the 28th week of gestation and sought correlates of measurements in the top quartile. Odds ratios of elevated concentrations were calculated for the most obvious correlates. Results: Infants born for maternal and foetal indications were more likely than their peers to have top quartile concentrations of IL‐beta, IL‐8, TNF‐alpha and ICAM‐1 on both days 21 and 28. Similarly, infants whose birthweight Z‐score was <−2 or between −1 and −2 were also more likely than their peers to have elevated concentrations of these proteins. Conclusion: Markers of systemic inflammation in the very preterm newborn during the third and fourth postnatal weeks are most strongly associated with maternal and foetal indications for (very preterm) delivery and their common correlate/consequence, foetal growth restriction.